Regionala skillnader i förtidspension och sjukfrånvaro med psykiatriska diagnoser i Sverige och Norge 1980-2000: samband med ålder, kön och tillgång till psykiatrisk vård - Andersson, Lena (Socialmedicinsk tidskrift, 2007)
Nedanstående artikel baseras på avhandlingen ”Regional differences in disability pension and sickness absence with psychiatric disorders in Sweden and Norway 1980-1998 – The influence of demography and access to psychiatric health care”. Avhandlingen försvarades på Göteborgs universitet maj 2006. Avhandlingen baserades på fyra tvärsnittsstudier och syftade till att förklara om regionala skillnader i antal förtidspensionärer med psykiatrisk diagnos kunde förklaras av ålder, kön eller tillgång till psykiatrisk vård. I avhandlingen användes epidemiologisk design och metod. Background: The incidence of disability pension and sickness absence with psychiatric diagnoses has increased and regional differences have been observed. Aim: To describe regional differences in disability pension and sickness absence with psychiatric disorders and analyse if they were due to age, sex or access to psychiatric health care. Method: The thesis was based on four cross sectional studies in Sweden and Norway. Data on sickness absence and disability pension was collected from National Statistics, data on psychiatric health care staff, beds and population data was collected from Statistics Sweden and Norway. Results: Regional differences in disability pension and sickness absence with psychiatric diagnoses could not be explained by age, sex or access to psychiatric health care. Men and women in Göteborg and men in Oslo, presented elevated risk ratios compared to national data as well as both sex in certain semi rural regions. There was an association between access to psychiatric health care and disability pension with psychiatric disorders, but it could not explain the regional differences previously found. An association was found between psychiatric health care staff and disability pension with psychiatric disorders. The cumulative incidence of disability pension with psychiatric disorders increased in the youngest age groups and the highest increase of sickness absence with psychiatric diagnoses was found among women in Oslo. Key words: Disability pension, sickness absence, psychiatric disorders, regional differences.